Bridging the digital divide in the adoption of digital financial services - Yiing Jia Loke; Helen Siew Heng Lee; Phaik Nie Chin (Journal of Asian Business and Economic Studies)
Purpose – As the digital economy expands, examining Malaysians’ acceptance of digital financial services (DFS) becomes imperative. The intricacies of DFS necessitate that consumers possess both financial knowledge (FK) and digital financial literacy (DFL) to utilize DFS effectively. This study examines FK and DFL across demographics and their impact on DFS usage, aiming to bridge the gap between intended and actual adoption. Design/methodology/approach – An online survey garnered 525 responses. Given that FK and DFL, DFS usage intention and actual usage were ordinally measured, ordered logistic regression was employed. Findings – Age aside, socio-demographics similarly affect financial knowledge and digital financial literacy. FK strongly drives both intended and actual digital financial service (DFS) use. However, the impact of DFL varies: awareness and understanding are key for both intention and use, but digital financial risk control knowledge is vital for actual use. Digital skills mainly influence intended, not actual, DFS usage. Originality/value – This research distinguishes between the impacts of FK and DFL on DFS adoption. Moreover, the study decomposes digital financial literacy into three fundamental components, yielding valuable insights for targeting specific knowledge domains to enhance DFS implementation.